Effect of vagus nerve stimulation paired with rehabilitation for upper limb function improvement after stroke: a systematic review and meta-analysis of randomized controlled trials. Issue 2 (24th November 2021) - Zhao, Kehong; Yang, Jiaen; Huang, Jiapeng; Zhao, Ziqi; Qu, Yun
Abstract : Vagus nerve stimulation (VNS) could potentially facilitate arm function recovery after stroke. The aim of this review was to evaluate the effect of VNS paired with rehabilitation on upper limb function recovery after stroke. We considered randomized controlled trials (RCTs) that used VNS paired with rehabilitation for the improvement of upper limb function after stroke and were published in English. Eligible RCTs were identified by searching electronic databases, including MEDLINE, Web of Science, Embase, CENTRAL and PEDro, from their inception until June 2021. Quality of included studies was assessed using PEDro score and Cochrane's risk of bias assessment. A meta-analysis was performed on the collected data. Five studies with a total of 178 participants met the inclusion criteria. Overall, the present meta-analysis revealed a significant effect of VNS on Fugl–Meyer Assessment for Upper Extremity (FMA-UE, MD = 3.59; 95% CI, 2.55–4.63; P < 0.01) when compared with the control group. However, no significant difference was observed in adverse events associated with device implantation between the invasive VNS and control groups (RR = 1.10; 95% CI, 0.92–1.32; P = 0.29). No adverse events associated with device use were reported in invasive VNS, and one was reported in transcutaneous VNS. This study revealed that VNS paired with rehabilitation can facilitate the recovery of upper limb function in patients with stroke on the basis of FMA-UE scores, but the long-term effects remain to be demonstrated.